Baculovirus display of single chain antibody (scFv) using a novel signal peptide - Kitidee K. (2014)
Background: Cells permissive to virus can become refractory to viral replication upon intracellular expression of single chain fragment variable (scFv) antibodies directed towards viral structural or regulatory proteins, or virus-coded enzymes. For example, an intrabody derived from MH-SVM33, a monoclonal antibody against a conserved C-terminal epitope of the HIV-1 matrix protein (MAp17), was found to exert an inhibitory effect on HIV-1 replication.Results: Two versions of MH-SVM33-derived scFv were constructed in recombinant baculoviruses (BVs) and expressed in BV-infected Sf9 cells, N-myristoylation-competent scFvG2/p17 and N-myristoylation-incompetent scFvE2/p17 protein, both carrying a C-terminal HA tag. ScFvG2/p17 expression resulted in an insoluble, membrane-associated protein, whereas scFvE2/p17 was recovered in both soluble and membrane-incorporated forms. When coexpressed with the HIV-1 Pr55Gag precursor, scFvG2/p17 and scFvE2/p17 did not show any detectable negative effect on virus-like particle (VLP) assembly and egress, and both failed to be encapsidated in VLP. However, soluble scFvE2/p17 isolated from Sf9 cell lysates was capable of binding to its specific antigen, in the form of a synthetic p17 peptide or as Gag polyprotein-embedded epitope. Significant amounts of scFvE2/p17 were released in the extracellular medium of BV-infected cells in high-molecular weight, pelletable form. This particulate form corresponded to BV particles displaying scFvE2/p17 molecules, inserted into the BV envelope via the scFv N-terminal region. The BV-displayed scFvE2/p17 molecules were found to be immunologically functional, as they reacted with the C-terminal epitope of MAp17. Fusion of the N-terminal 18 amino acid residues from the scFvE2/p17 sequence (N18E2) to another scFv recognizing CD147 (scFv-M6-1B9) conferred the property of BV-display to the resulting chimeric scFv-N18E2/M6.Conclusion: Expression of scFvE2/p17 in insect cells using a BV vector resulted in baculoviral progeny displaying scFvE2/p17. The function required for BV envelope incorporation was carried by the N-terminal octadecapeptide of scFvE2/p17, which acted as a signal peptide for BV display. Fusion of this peptide to the N-terminus of scFv molecules of interest could be applied as a general method for BV-display of scFv in a GP64- and VSV-G-independent manner. © 2010 Kitidee et al; licensee BioMed Central Ltd.